Application of expert evaluation methods in determining the significance of criteria for usability of railway traction rolling stock - Maskeliūnaitė, Lijana; Meilus, Laurynas; Sivilevičius, Henrikas (Transport, 2023)
Railway rolling stock must meet the requirements related to its use in the transportation process. The significance of these requirements can be determined using expert testing methods. The current research offers a framework of 9 criteria, which have been developed by the authors of the study, and which contribute to a comprehensive assessment of their importance and priority in relation to each other using expert evaluation methods. The normalised weights of the criteria were determined using Average Rank Transformation Into Weight Linear (ARTIW-L), Average Rank Transformation Into Weight Non-linear (ARTIW-N) and Direct Percentage Weight (DPW) methods. The criteria were given ranks and percentage weights by 18 experts with consistent opinions, which made it reasonable to consider the average of the experts’ opinions as the outcome of the task. The normalised weights of the criteria have shown that the most important issues for the experts included passenger and crew safety (0.1619), passenger and train staff ride comfort (0.1330) and environmental protection (0.1201). The least important criteria for the experts cover the range per one electric charge or full tank of fuel (0.0776), the dynamic performance of the traction rolling stock (0.0849), and the purchase price, the rebate system, the duration of the warranty period (0.0911). The other 3 criteria are of medium importance. The outcomes of this study can be used in deciding on the best alternative for rail traction rolling stock.